The Class : Living and Learning in the Digital Age - Livingstone, Sonia M.; Sefton-Green, Julian (Book collections on Project MUSE., 2016)
Do today's youth have more opportunities than their parents? As they build their own social and digital networks, does that offer new routes to learning and friendship? How do they navigate the meaning of education in a digitally connected but fiercely competitive, highly individualised world? Based upon fieldwork at an ordinary London school, 'The Class' examines young people's experiences of growing up and learning in a digital world. It explores youth values, teenagers' perspectives on their futures, and their tactics for facing the opportunities and challenges that lie ahead.